Research of possibility of gamma-spectrometry of coals in field environment - O. A. Bezshyyko; S. A. Karpenko; I. A. Maliuk; O. I. Nasvit; V. M. Pryymak; E. E. Petrosian; K. A. Tyschenko (Ядерна фізика та енергетика)
By the method of Monte Carlo apparatus gamma-spectrums were generated for the model of coal mass averaged on physical and chemical properties and detectors located in it on the base of stintillation crystals of NaI and LaBr3. As a result of processing of the generated gamma-spectrums using of the standard programs possibilities of gammaspectrometry method of measuring of natural radio-activity of coals in field environment were defined.